Effect of Profitability and Operating Leverage on Capital Structure in Property, Real Estate, and Building Construction Companies - Muhammad Kurniawan; Erna Retna Rahadjeng; Sandra Irawati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The purpose of this research is to determine the effect of profitability and operating leverage on the capital structure. This type of research is associative research with the object of research in property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the period 2017-2019. This study uses a purposive sampling method, namely all companies listed on the Indonesia Stock Exchange for the 2017-2019 period of 126 obtained a sample of 96 companies. The data analysis technique uses Multiple Linear Regression Analysis with the help of SPSS26 software. The results showed that profitability and operating leverage simultaneously influence the capital structure and profitability has a parallel effect on the capital structure while operating leverage has no partial effect on the capital structure.